Analysis of Tax Planning Implementation to Minimize Value Added Tax Load - Eni Wahyu Setyaningsih; Rizki Indrawan (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
As a sizable source of state revenue, of course taxes are also a problem for the community, because taxes are in almost every activity we carry out, starting from Value Added Tax (VAT), Income Tax, and Sales Tax on Luxury Goods, and other taxes. This consider points to see how the execution of charge arranging to play down the assess burden payable esteem included assess at PT. Mobar Sarana Energi. The object of this research is tax planning and minimizing the tax burden payable for value added tax. The research method used was a qualitative study through a case study method, and the data obtained were both primary and secondary data. Primary data from interviews, observations and documents, then secondary data from company records or sales tax data. From the results of research in 2019 and 2020, it was found that by implementing tax planning on VAT with the mechanism of delaying input tax credits and compensation, it was able to equalize VAT while purchasing taxable goods/ services with VAT would be able to reduce the tax burden owed by 6.8 percent.